Sumber Daya Manusia Sebagai Resources Pengembangan Dan Tantangan Perilaku Organisasi - Tono Wartono (LPPM UNU CIREBON, 2025)
Study purpose. This study aims to analyse the strategic role of human resources (HR) in organisational development and identify behavioural challenges encountered in its management.Materials and methods. The method used is a literature study with a descriptive qualitative approach, which explores theories and findings from previous studies related to HR management and organisational behaviour. Results. The research findings indicate that HR plays a central role not only as implementers of policies but also as agents of change, innovators, and guardians of a healthy organisational culture. However, behavioural challenges such as interpersonal conflicts, resistance to change, and low work motivation pose serious obstacles to achieving organisational goals.Conclusion. effective HR management requires adaptive strategies focused on competency development, transformative leadership, employee empowerment, and the creation of a positive and inclusive work culture.